Complete the equation so that it has infinite solutions.(1 point)
4x+10= ____x+ _____
9 answers
4x+10= 4x+10
Complete the equation so that it has no solution.(1 point)
−7x−12= ____x+12
−7x−12= ____x+12
−7x−12= −7x+12
Solve for x to determine if the equation has one, none, or infinite solutions.
6(2x+4)−24=12x
(1 point)
Responses
The equation has one solution: x=−20.
The equation has infinite solutions.
The equation has no solution.
The equation has one solution: x=0.
6(2x+4)−24=12x
(1 point)
Responses
The equation has one solution: x=−20.
The equation has infinite solutions.
The equation has no solution.
The equation has one solution: x=0.
To determine the solution(s), let's solve the equation step by step:
6(2x+4)−24=12x
Start by distributing the 6:
12x + 24 - 24 = 12x
Combine like terms:
12x = 12x
We can see that the variable x is on both sides of the equation and the coefficients are the same. This means that all terms cancel out on both sides, resulting in an equation with infinite solutions.
Therefore, the equation has infinite solutions.
6(2x+4)−24=12x
Start by distributing the 6:
12x + 24 - 24 = 12x
Combine like terms:
12x = 12x
We can see that the variable x is on both sides of the equation and the coefficients are the same. This means that all terms cancel out on both sides, resulting in an equation with infinite solutions.
Therefore, the equation has infinite solutions.
Solve for x
to determine if the equation has one, none, or infinite solutions.
9(x+1)=3(5x+1)−12
(1 point)
Responses
The equation has infinite solutions.
The equation has infinite solutions.
The equation has one solution: x=3
.
The equation has one solution: x equals 3 .
The equation has one solution: x=0
.
The equation has one solution: x equals 20 .
The equation has no solution.
to determine if the equation has one, none, or infinite solutions.
9(x+1)=3(5x+1)−12
(1 point)
Responses
The equation has infinite solutions.
The equation has infinite solutions.
The equation has one solution: x=3
.
The equation has one solution: x equals 3 .
The equation has one solution: x=0
.
The equation has one solution: x equals 20 .
The equation has no solution.
To determine the solution(s), let's solve the equation step by step:
9(x+1)=3(5x+1)−12
Start by distributing on both sides:
9x + 9 = 15x + 3 - 12
Combine like terms:
9x + 9 = 15x - 9
Now, let's isolate the variable terms on one side and the constant terms on the other side. We can do this by subtracting 9x and adding 9 to both sides:
9 = 15x - 9x - 9
Combine like terms:
9 = 6x - 9
Add 9 to both sides:
18 = 6x
Divide both sides by 6:
3 = x
Therefore, the equation has one solution: x = 3.
9(x+1)=3(5x+1)−12
Start by distributing on both sides:
9x + 9 = 15x + 3 - 12
Combine like terms:
9x + 9 = 15x - 9
Now, let's isolate the variable terms on one side and the constant terms on the other side. We can do this by subtracting 9x and adding 9 to both sides:
9 = 15x - 9x - 9
Combine like terms:
9 = 6x - 9
Add 9 to both sides:
18 = 6x
Divide both sides by 6:
3 = x
Therefore, the equation has one solution: x = 3.
Complete the equation so that it has no solution.(1 point)
5x+12= _____x+9
5x+12= _____x+9
To make the equation have no solution, we need to have the same coefficients on both sides, but different constants.
Therefore, we can complete the equation as:
5x + 12 = 5x + 9
Therefore, we can complete the equation as:
5x + 12 = 5x + 9